Diagnosis of viral gastroenteritis: limits and potential of currently available procedures - Francesca Sidoti; Massimo Rittà; Cristina Costa; Rossana Cavallo (Journal of Infection in Developing Countries)
The diagnostic approaches to viral gastroenteritis have evolved substantially over the past decades because of the advances in detection methods, the emergence of new pathogens, and the increase in diarrhea hospitalizations attributed to viruses, especially in young children in non-industrialized countries. Overall, these factors have lead to a relevant improvement of types and operating characteristics of diagnostic methods (including sensitivity and specificity), as well as turnaround time. In this review, clinical and laboratory approaches to the diagnosis of viruses causing gastroenteritis are presented; in particular, specimen collection and detection methods are reviewed and discussed, taking into account performance and limitations.